SOVEREIGNS, UPSTREAM CAPITAL FLOWS, AND GLOBAL IMBALANCES. Issue 5 (October 2014) - Alfaro, Laura; Kalemli‐Ozcan, Sebnem; Volosovych, Vadym
Abstract We construct measures of net private and public capital flows for a large cross‐section of developing countries considering both creditor and debtor side of the international debt transactions. Using these measures, we demonstrate that sovereign‐to‐sovereign transactions account for upstream capital flows and global imbalances. Specifically, we find that (i) international net private capital flows (inflows minus outflows of private capital) are positively correlated with countries' productivity growth, (ii) net sovereign debt flows (government borrowing minus reserves) are negatively correlated with growth only if net public debt is financed by another sovereign, (iii) net public debt financed by private creditors is positively correlated with growth, (iv) public savings are strongly positively correlated with growth, whereas correlation between private savings and growth is flat and statistically insignificant. These empirical facts contradict the conventional wisdom and constitute a challenge for the existing theories on upstream capital flows and global imbalances.